Germline genetic variation in ETV6 and risk of childhood acute lymphoblastic leukaemia: a systematic genetic study. Issue 16 (December 2015) - Moriyama, Takaya; Metzger, Monika L; Wu, Gang; Nishii, Rina; Qian, Maoxiang; Devidas, Meenakshi; Yang, Wenjian; Cheng, Cheng; Cao, Xueyuan; Quinn, Emily; Raimondi, Susana; Gastier-Foster, Julie M; et al.
Summary: Background: Hereditary predisposition is rarely suspected for childhood acute lymphoblastic leukaemia (ALL). Recent reports of germline ETV6 variations associated with substantial familial clustering of haematological malignancies indicated that this gene is a potentially important genetic determinant for ALL susceptibility. Our aims in this study were to comprehensively identify ALL predisposition variants in ETV6 and to determine the extent to which they contributed to the overall risk of childhood ALL. Methods: Whole-exome sequencing of an index family with several cases of ALL was done to identify causal variants for ALL predisposition. Targeted sequencing of ETV6 was done in children from the Children's Oncology Group and St Jude Children's Research Hospital front-line ALL trials. Patients were included in this study on the basis of their enrolment in these clinical trials and the availability of germline DNA. ETV6 variant genotypes were compared with non-ALL controls to define ALL-related germline risk variants. ETV6 variant function was characterised bioinformatically and correlated with clinical and demographic features in children with ALL. Findings: We identified a novel non-sense ETV6 variant (p.Arg359X) with a high penetrance in an index family. Subsequent targeted sequencing of ETV6 in 4405 childhood ALL cases identified 31 exonic variants (four non-sense, 21 missense, one splice site, and five frameshift variants) that were potentially related to ALL risk in 35 cases (1%). 15 (48%) of 31 ALL-related ETV6 variants clustered in the erythroblast transformation specific domain and were predicted to be highly deleterious. Children with ALL-related ETV6 variants were significantly older at leukaemia diagnosis than those without (10·2 years [IQR 5·3–13·8] vs 4·7 years [3·0–8·7]; p=0·017). The hyperdiploid leukaemia karyotype was highly over-represented in ALL cases harbouring germline ETV6 risk variants compared with the wild-type group (nine [64%] of 14 cases vs 538 [27%] of 2007 cases; p=0·0050). Interpretation: Our findings indicated germline ETV6 variations as the basis of a novel genetic syndrome associated with predisposition to childhood ALL. The development of recommendations for clinical interventions and surveillance for individuals harbouring ALL-related ETV6 variants are needed. Funding: US National Institutes of Health and American Lebanese Syrian Associated Charities.